Risk factors that may signify a propensity to the use of drugs in students at a public university - Silva, Meire Luci da [UNESP]; Santos, Nathalia Marina Ribeiro dos [UNESP]; Barnabé, Viviani; Valenti, Vitor Engrácia [UNESP] (My University, 2013)
Introduction: We sought to evaluate the risk factors that may increase the propensity to use licit and illicit drugs among students at a public university. Methods: The project involved students (n = 268) enrolled in the first and fourth years of courses in the areas of the social and biological sciences at a public university. Data collection was conducted by means of self-administered, semistructured questionnaires, based on such standardized assessment instruments as Audit, Assist, Cage and Duse. Collected data were analyzed quantitatively by calculating the percentages and evaluating the data in terms of categories of risk, classifying them by age, gender, religion, schooling, use (before or after entering university) and contexts of use. By means of this survey the researchers were able to correlate the use of drugs to the risk factors that might increase the students’ propensity to use these substances. Results: The results revealed a high proportion of current drug-using students, but showed no significant differences between the first and fourth year students as regards contexts of use. However, 67% of students regarded the university environment as encouraging the use of drugs. Students pointed to such major risk factors as friends’ and fellow-students’ influence, university parties, excessive curiosity and desire to experiment. Conclusion: Due to the high rate of drug use among university students, by the determination of the risk factors related to the university environment and also knowing that the process of addiction is one of growing chemical dependence, the importance of the development and implementation of public health policies at all levels, especially in terms of approaches and specific interventions addressing this population, should be noted.

Objetivo: Buscou-se avaliar os fatores de risco que podem induzir o uso de drogas lícitas e ilícitas por estudantes de uma universidade pública. Método: o projeto os alunos envolvidos (n = 268) matriculados no primeiro e quarto anos de cursos nas áreas das ciências sociais e biológicas de uma universidade pública. A coleta de dados foi realizada por meio de questionário semiestruturado e de autopreenchimento, com base em tais instrumentos de avaliação padronizados como Audit, Assist, Cage e Duse. Os dados coletados foram analisados quantitativamente por meio do cálculo das percentagens e avaliar os dados em termos de categorias de risco, classificando-os por idade, sexo, religião, escolaridade, uso (antes ou depois de entrar na universidade) e contextos de uso. Por meio deste estudo os pesquisadores foram capazes de correlacionar o uso de drogas para os fatores de risco que podem aumentar a propensão dos alunos a usar essas substâncias. Resultados: Os resultados revelaram alto índice no número de alunos que atualmente usam drogas, porém não apontaram diferenças significativas entre alunos de 1º ano e 4º anos em relação às situações de uso. No entanto, 67% dos alunos consideraram o ambiente universitário como estimulante ao uso de drogas. Foram apontados como fatores de risco: influência de amigos e colegas de universidade, festas universitárias, a curiosidade e alegria. Conclusão: Devido ao alto índice do uso de drogas entre estudantes universitários e aos fatores de riscos que influenciam o uso estarem relacionado ao ambiente universitário, nota-se a importância de uma atenção voltada a esta população, pois sabese que a dependência química é um processo de instalação gradativa. Os resultados apontam a necessidade de intervenções específicas para esta população através da implantação de programas de prevenção, conscientização e de tratamento.
Fatores de risco que podem induzir o uso de drogas por estudantes de uma universidade pública
Keywords: dependência química; estudantes; fatores de riscos